Differential visual system organization and susceptibility to experimental models of optic neuropathies in three commonly used mouse strains. (April 2016) - De Groef, Lies; Dekeyster, Eline; Geeraerts, Emiel; Lefevere, Evy; Stalmans, Ingeborg; Salinas-Navarro, Manuel; Moons, Lieve
Abstract: Mouse disease models have proven indispensable in glaucoma research, yet the complexity of the vast number of models and mouse strains has also led to confusing findings. In this study, we evaluated baseline intraocular pressure, retinal histology, and retinofugal projections in three mouse strains commonly used in glaucoma research, i.e. C57Bl/6, C57Bl/6-Tyr c, and CD-1 mice. We found that the mouse strains under study do not only display moderate variations in their intraocular pressure, retinal architecture, and retinal ganglion cell density, also the retinofugal projections to the dorsal lateral geniculate nucleus and the superior colliculus revealed striking differences, potentially underlying diverging optokinetic tracking responses and visual acuity. Next, we reviewed the success rate of three models of (glaucomatous) optic neuropathies (intravitreal N-methyl-d -aspartic acid injection, optic nerve crush, and laser photocoagulation-induced ocular hypertension), looking for differences in disease susceptibility between these mouse strains. Different genetic backgrounds and albinism led to differential susceptibility to experimentally induced retinal ganglion cell death among these three mouse strains. Overall, CD-1 mice appeared to have the highest sensitivity to retinal ganglion cell damage, while the C57Bl/6 background was more resistant in the three models used. Highlights: C57Bl/6, C57Bl/6-Tyr c, and CD-1 mice were studied. Intraocular pressure, retinal histology, and RGC density varied in these strains. Different retinofugal projections to the dLGN and SC were observed. Optokinetic tracking responses and visual acuity were strikingly different. The three strains were differentially susceptible to experimental RGC death.